Azimuthally Polarized Radial Emission from a Quantum Dot Fiber Laser - Zhang, Nan (2017)
We demonstrate an azimuthally polarized radial emission with zero angular momentum from a CdSe/CdZnS/ZnS quantum dot (QD) fiber laser. This fiber laser is realized by axially pumping the QD-doped gain plug infiltrated in the hollow cavity of a multilayer photonic band-gap fiber. The cylindrically symmetric radial emission is registered as a perfect ring-shaped pattern in the far field. The lasing threshold is measured to be ∼238 μJ/pulse, and the quality factor is calculated to be ∼4000. The unique radial emission from the resulting QD fiber laser offers a fundamental solution for the development of omnidirectional displays and light sources for biomedical analysis and phototherapy with minimal invasion.